Effects of Genotype, Explants Type and Growth Regulators on Organogenesis in Carnation - Sharma, Puja; Dhiman, S. R.; Gupta, Y. C.; Sharma, Priyanka; Gautam, Bharti (International Journal of Bio-resource and Stress Management, 2016)
In vitro organogenesis and shoot multiplication protocol of carnation (Dianthus caryophyllus L.) cultivars Madras, Tempo, Dark Rendez Vous and Raggio de Sole was developed using apical and nodal sections of shoots as explants. It has been found that in vitro shoot multiplication is highly variable and genotype dependant. The earliest establishment of shoot sections (8.24 days) with maximum number of shoots explants-1 (2.16) was recorded in MS medium supplemented Benzyl-6-adenine 2 mg l-1. Nodal sections as explants produced more number of shoots as compared to apical portion when inoculated on MS medium supplemented with Benzyl-6-adenine (2 mg l-1). In case of cultivars, earliest shoot establishment (8.97 days) was noticed in cv. Raggio de Sole. On the other hand, number of shoots explant-1 was found to be maximum (2.00) in cv. Dark Rendez Vous. MS medium supplemented with BA 2 mg l-1, GA3 1 mg l-1 and NAA 0.1 mg l-1 was found to be the most effective medium for shoot multiplication, producing 6.74 shoots shoot-1 with longer shoots (3.16 cm). Shoot proliferation was recorded maximum (6.92 shoots shoot-1) in cv. Raggio de Sole, whereas, maximum length of shoots in multiplication medium (3.51 cm) was observed in cv. Tempo. The regenerated shoots were rooted on MS medium added with NAA 2 mg l-1. The rooted plantlets were hardened in medium containing cocopeat and sand (1:1, v/v) and successfully transferred to field conditions.